PENDIDIKAN MITIGASI DALAM MENGURANGI DAMPAK BENCANA DI KOTA PADANG - Marzuki Samion (BEST Journal (Biology Education, Sains and Technology), 2021)
Disaster response education and pre-disaster mitigation are part of the government's efforts to reduce the impact of disasters on the community, especially in areas that have a large potential for disasters such as the city of Padang, West Sumatra. Learning from past experiences and realizing that Indonesia's geographical location is prone to earthquakes, disaster mitigation education should be an important part of teaching and learning activities in schools. The Padang city government in principle has tried to anticipate the occurrence of disasters in disaster-prone areas, including providing and facilitating the location of gathering points that may be used; informing evacuation routes that can be used by the community through maps of evacuation routes caused by earthquakes and tsunamis, and implement disaster mitigation through education and training in schools.